Do changes in microglial status underlie neurogenesis impairments and depressive-like behaviours induced by psychological stress? A systematic review in animal models - Nieto-Quero, Andrea; Chaves-Peña, Patricia; Santín-Núñez, Luis Javier; Pérez-Martín, Margarita; Pedraza-Benítez, María del Carmen (Elsevier, 2021)
Stress may have a negative effect on mental health and is the primary environmental risk factor in the aetiology of depression. Nevertheless, the neurobiological mechanisms underlying this mood disorder remain poorly characterized. The hippocampus is a target structure of the adverse effects of stress, and hippocampal neuro- genesis plays a crucial role. However, we do not know the mechanisms by which stress impacts neurogenesis. Recent studies indicate that changes in neuroinflammation, primarily via microglial cells, may play an essential role in this process. However, the relationship between stress, microglial changes, and alterations in neurogenesis and their involvement in the development of depression is poorly characterized. For this reason, this systematic review aims to synthesise and evaluate current studies that have investigated the relationship between these variables. Taken together, the revised data, although not entirely conclusive, seem to suggest that microglial changes induced by psychological stress regulate neurogenesis and in turn may be responsible for the devel- opment of depressive-like behaviours, but other factors that influence these stressful experiences should not be dismissed.
Keywords: Neurobiología del desarrollo; Psychosocial stress; Neurogenesis; Microglia; Neuroinflammation; Depression; Animal models; Systematic review